A Cell‐free DNA Barcode‐Enabled Single‐Molecule Test for Noninvasive Prenatal Diagnosis of Monogenic Disorders: Application to β‐Thalassemia. Issue 11 (1st April 2019) - Yang, Xingkun; Zhou, Qinghua; Zhou, Wanjun; Zhong, Mei; Guo, Xiaoling; Wang, Xiaofeng; Fan, Xin; Yan, Shanhuo; Li, Liyan; Lai, Yunli; Wang, Yongli; Huang, Jin; et al.
Abstract: Noninvasive prenatal testing of common aneuploidies has become routine over the past decade, but testing of monogenic disorders remains a challenge in clinical implementation. Most recent studies have inherent limitations, such as complicated procedures, a lack of versatility, and the need for prior knowledge of parental genotypes or haplotypes. To overcome these limitations, a robust and versatile next‐generation sequencing‐based cell‐free DNA (cfDNA) allelic molecule counting system termed cfDNA barcode‐enabled single‐molecule test (cfBEST) is developed for the noninvasive prenatal diagnosis (NIPD) of monogenic disorders. The accuracy of cfBEST is found to be comparable to that of droplet digital polymerase chain reaction (ddPCR) in detecting low‐abundance mutations in cfDNA. The analytical validity of cfBEST is evidenced by a β‐thalassemia assay, in which a blind validation study of 143 at‐risk pregnancies reveals a sensitivity of 99.19% and a specificity of 99.92% on allele detection. Because the validated cfBEST method can be used to detect maternal‐fetal genotype combinations in cfDNA precisely and quantitatively, it holds the potential for the NIPD of human monogenic disorders. Abstract : A cell‐free DNA barcode‐enabled single‐molecule test (cfBEST), a next‐generation sequencing‐based molecule counting system, is developed for the noninvasive prenatal diagnosis (NIPD) of monogenic disorders. The accuracy of cfBEST is evidenced by a β‐thalassemia assay, in which a validation study reveals a concordance rate of 99.78%. cfBEST holds the potential to be a general method for the NIPD of monogenic disorders.